(untitled) (Medical Forum Monthly, 2020)
Objective: To study the association of clinical features & comorbidity among Covid-19 patients admitted in tertiary care hospital. Study Design: Cross-sectional study Place and Duration of Study: This study was conducted at the ABWA hospital and research center attached with Abwa Medical College, Faisalabad for the period of four months from April to July, 2020. Materials and Methods: Total 142 admitted Covid-19 patients were selected as participants to assess the range of symptoms experienced during active phase of infection. Results: Out of total 142 participants, 87.3 %( n=124) complaint of shortness of breath, 57.7%(n=82) had fever & 43.3% (n=62) had cough,27.5%(n=39) reported of body aches as compared to 14.1% (n=20) who had loose motions & 3.5%(n=5) who experienced irritability. Regarding comorbidity,49.3%(n=70) patients had Diabetes Mellitus,33.1%(n=47) Hypertension, 10.6%(n=15) Ischemic heart disease & 2.8%(n=4) had Chronic kidney disease. Conclusion: During the pandemic of corona infection, majority of the symptomatic patients admitted in hospital had pre-existing health issues i.e. Diabetes, Hypertension, Renal diseases & respiratory involvement. Moreover, the concurrence of Covid-19 infection with medical syndrome serve as a vital prognosis factor linked with complications with multi organ involvement, unexpected outcome & longer hospital stay. This implies that health care emergency services should be formulated and implemented in a way where supervised intensive care should be provided to the most vulnerable group. Moreover, extensive awareness campaigns should be carried out to identify the group at risk of mortality.